A novel guided approach to radiofrequency ablation of thyroid nodules: the Toronto Sunnybrook experience - Sarkis, Leba Michael; Higgins, Kevin; Enepekides, Danny; Eskander, Antoine (Frontiers in Endocrinology, 2024)
Introduction: Thyroid nodules are extremely common being detected by ultrasonography in up to 67% of the population, with current surgical tenet maintaining that lobectomy is required for large symptomatic benign nodules or autonomously functionally nodules resulting in a risk of hypothyroidism or recurrent laryngeal nerve injury even in high volume centres. The introduction of radiofrequency ablation (RFA) has allowed thermal ablation of both benign and autonomously functioning thyroid nodules with minimal morbidity. The moving shot technique is the most well-established technique in performing RFA of thyroid nodules, and has proven to be safe, efficacious, accurate and successful amongst experienced clinicians. The purpose of this article to propose the use of a novel guide when performing RFA of thyroid nodules in clinical practice utilizing the moving shot technique. Methods: The technique proposed of RFA involves the use of a 10MHz linear ultrasound probe attached to an 18G guide which provides robust in line visualisation of a 7cm or 10cm radiofrequency probe tip (STARmed, Seoul, Korea) utilizing the trans isthmic moving shot technique. A geometric analysis of the guide has been illustrated diagrammatically. Results: The use of an 18G radiofrequency probe guide (CIVCO Infiniti Plus™ Needle Guide) maintains in line visualisation of the radiofrequency probe over a cross sectional area up to 28cm2, facilitating efficient and complete ablation of conceptual subunits during RFA of thyroid nodules. Discussion: Radiofrequency ablation of thyroid nodules can be performed safely and effectively using the novel radiofrequency probe guide proposed which we believe potentially improves both accuracy and overall efficiency, along with operator confidence in maintaining visualisation of the probe tip, and hence we believe provides a valuable addition to the armamentarium of clinicians wishing to embark on performing RFA of thyroid nodules.